Renewing the Yolŋu ‘Bothways’ philosophy: Warramiri transculturation education at Gäwa - van Gelderen, Ben; Guthadjaka, Kathy (The Australian Journal of Indigenous Education, 2019)
Abstract ‘Bothways’ was an expression first utilised by Yolŋu educators in the late 1980s to convey the profound intercultural epistemological foundations of Yolŋu society that should also apply to modern Balanda (white) schooling systems. Despite the pressures from national, standardised curriculum and assessment regimes, ‘Bothways’ has not been abandoned by remote Yolŋu communities in the 21st century. In this paper we briefly revisit the first iterations of the ‘Bothways’ philosophy to demonstrate its symmetry with the Yolŋu transculturation heritage (of the Warramiri in particular), developed through many centuries of contact with sea-faring visitors. Lastly, we present data from community research at Gäwa, a Warramiri homeland on Elcho Island, which demonstrates that through a series of ‘multiple balances’, negotiation around issues of bilingual pedagogy, cultural knowledge transmission, parental engagement and student–teacher dynamic continues to renew the ‘Bothways’ approach.